Proses Integrasi Pembelajaran Berbantuan Teknologi pada Peserta Didik Kelas IV di SDN Kedaleman IV Kota Cilegon - Ayu, Cantika Putri; Hakim, Zerri Rahman; Pribadi, Reksa Adya (CV. Rayyan Dwi Bharata, 2024)
This research is based on the development and progress of technology and the internet which is increasingly rapidly, the internet is the most complete source of information. The internet is actually able to provide many conveniences for its users, this convenience should also be felt in the world of education where the internet can be used as a learning tool. This study aims to provide an overview of the use of internet media as a learning tool. As we know that the Internet is increasingly being used as a medium of learning in schools because it is able to provide convenience for teachers and students so that learning can be carried out anytime and anywhere. This study uses a descriptive qualitative approach, to obtain data in the field, research use data collection techniques by means of interviews, documentation observations and the subjects of this research are the principal, homeroom teacher and fourth grade students at SDN Kedaleman IV Cilegon City. The learning process begins with preparation, the Internet is used during distance learning, evaluation activities and material strengthening. Utilization of the internet makes it easier for students to understand the material, be more active and have a better personality.